A mudança da linguagem matemática para a liguagem web e as suas implicações na interpretação de problemas matemáticos - Kalinke, Marco Aurélio (2009)
The core goal of this research is to verify the language usually applied in web ambients, to the detriment of the mathematical symbolic language, can interfere in the mathematical problems interpretation formulated with the use of the Web language. For answering this question we realized a quality research mixed with quantity aspects that can contribute to understand the phenomena s involved. For developing this work we searched theoretical basement in Levy s works, that deal with the technologies evolution and in Kenski, when his works refer to the relation between technologies and education. Borba and Tikhomirov give us support between the relations of cognition and learning when the new technologies are being used. Cybis, Gamez and Ramos give us the basement for the ergonomics analysis and AVA legibly. Salmazo, Hoelzel and Nielsen are presents in aspects related to communication. Others authors have permeated the discussion in a sharp way for the comprehension of specific situations. The analisys of the data researched permitted us to conclude that the language usually used in web ambients, conjugated in a media that it is inserts, can bring problems of interpretation and comprehension from the statement of the problems. We realized that difficulties are more evident when it´s used the computer medium than the paper medium. We concluded that the paper medium can facilitate the solution of mathematical problems, if compared to the computer medium, that subjects manage to interpret in a correct way the statements proposed to the language usually used in web ambients , they manage to use the computer to solve problems that use mathematical symbology as long as they have access to necessary resources and the union between the computer medium to the language usually used in web ambients presented difficulties to the subjects participants in the survey. For remedying or minimize these problems we suggest that have an improvement in the communication between the user and the text presented to it. For complying this suggestion the texts used in AVAs must be elaborated carefully to be scannable according to Nielsen conception. The use of these resources when the text is being written it´s not the guarantee of the elimination from the problems observed, but can open a new perspective of the analysis for these problems, since that new forms and characteristics of writing arise new necessities of behaving analysis from the subjects front the problems presented that are formulated with basis in these new possibilities